2013
DOI: 10.1371/journal.pone.0061097
|View full text |Cite
|
Sign up to set email alerts
|

Can Inpatient Hospital Experiences Predict Central Line-Associated Bloodstream Infections?

Abstract: BackgroundFactors that increase the risk of central line-associated bloodstream infections (CLABSIs) are not fully understood. Recently, Hospital Compare began compiling data from hospital-required reporting to the CDC's National Healthcare Safety Network on CLABSIs in intensive care units (ICUs), at over 4,000 Medicare-certified hospitals in the United States, and made this data accessible on a central website. Also available on the same website are results from the Hospital Consumer Assessment of Healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…Those chosen were overall hospital rating, willingness to recommend the hospital, communication with doctors, and responsiveness of staff, as others have demonstrated that these are representative of the HCAHPS questionnaire and are associated with technical quality of care. 8,10,15,17,18,22 Most of the relationships investigated demonstrated an association between higher patient satisfaction scores and better quality of medical care. Of the 52 possible relationships studied, 29 (56%) demonstrated a significant trend (P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…Those chosen were overall hospital rating, willingness to recommend the hospital, communication with doctors, and responsiveness of staff, as others have demonstrated that these are representative of the HCAHPS questionnaire and are associated with technical quality of care. 8,10,15,17,18,22 Most of the relationships investigated demonstrated an association between higher patient satisfaction scores and better quality of medical care. Of the 52 possible relationships studied, 29 (56%) demonstrated a significant trend (P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary data on risk factors have limitations in terms of generalizability. [5][6][7]9 We found independent predictors of CLABSI included duration of CVC presence and more frequent CVC access-specifically, higher number of lab tests drawn. Although we found an association between number of intravenous medications given and CLABSI in bivariate analysis, this association was not seen in our multivariate analysis, possibly owing to limited power.…”
Section: Resultsmentioning
confidence: 76%
“…This theory might also explain greater observed awareness of CVCs among intensivists, because lower patient–provider ratios, coupled with standardization of process and a culture that is highly attuned to these devices, may make CVCs more “visible” in critical care settings (12). Conversely, the absence of such culture and the heterogeneous composition of care teams in non-ICU settings may inadvertently foster lack of CVC awareness (10, 20, 21). …”
Section: Discussionmentioning
confidence: 99%